DEVELOPMENT OF A HALAL SEAFOOD CULINARY TOURISM MODEL AS THE MAIN ATTRACTION OF ISLAMIC TOURISM DESTINATIONS IN ACEH: INTEGRATION OF PROCESSING TECHNOLOGY, HALAL CERTIFICATION, AND MUSLIM TOURIST EXPERIENCE - Eka Octavian Pranata; Aula Sakinah; Isnaliana (El-Mubarak: Islamic Studies Journal, 2026)
This study develops an integrated model of halal seafood culinary tourism (HSCT-Model) as a primary competitive attraction for Islamic tourism destinations in Aceh Province, Indonesia. The research integrates three disciplinary dimensions: halal seafood processing technology, halal certification management, and Muslim tourist experience. A sequential explanatory mixed-methods design was employed, comprising: (1) laboratory analysis of three signature Acehnese seafood products (keumamah, eungkot paya, and dendeng ikan tenggiri); (2) a structured survey of 220 Muslim tourists (domestic and international) analysed using Structural Equation Modelling via Partial Least Squares (SEM-PLS, SmartPLS 4.0); and (3) two-round stakeholder Focus Group Discussions (FGDs) for model validation. Findings reveal that halal certification trust exerts the strongest influence on Muslim tourist satisfaction (β = 0.421, p < 0.001), while processing technology quality mediates the relationship between halal compliance and food tourism experience (β = 0.318, p < 0.01). Laboratory analysis confirms that all three products comply with SNI halal food safety standards. The resultant HSCT-Model integrates four pillars: halal processing standards, certification traceability, culinary experience design, and digital marketing for Muslim travellers. This model offers a replicable governance framework for Muslim-majority coastal destinations seeking to leverage halal food heritage as a strategic tourism differentiator.